Estimation of the Coefficients of the Equation of Acoustic Target Strength Based on the Morphology of Coregonus migratorius (Georgi, 1775) Swim Bladder - P. N. Anoshko; M. M. Makarov; S. B. Popov; A. I. Degtev; N. N. Denikina; E. V. Dzyuba (Юг России: экология, развитие)
Aim. The aim of the study was to estimate the coefficients of the equation TSmax=f(SL) considering the characteristics of an acoustic scattering model based on the morphological characteristics of the swim bladder of the Coregonus migratorius (Georgi, 1775). Material and Methods. Ninety‐nine living specimens of C. migratorius served as the study material. For each specimen, the target strength in the cage was measured using an Kongsberg Simrad EY500 echo sounder and the morphology of the swim bladder was studied. Measurements, analysis of images and data were conducted using Image Pro 6.0. Excel and SciLab software resources. Results. We determined the main morphological characteristics of the swim bladder in C. migratorius as well as the correspondence of its dimensions and proportions in relation to the length of the fish’s body. The coefficients of the equation TS=20log(SL)‐60, calculated on the results of the acoustic scattering model of a prolate spheroid, agree well with the coefficients calculated from maximum values obtained in the cage experiment. During the conversion of the coefficients relating to the allometric changes in the length of the swim bladder relative to fish length, the equation TS=23.2log(SL)‐64.4 was obtained. A comparative analysis of the available equations of the target strength for C. migratorius with those obtained in the study was undertaken. Conclusion. The equation obtained on the model of the swim bladder as a prolate spheroid adequately describes the dependence of the maximum values of the target strength on the body length of the C. migratorius and confirms the previously obtained dependence by maximum values of TS in the cage experimental conditions and can serve as a basis for further theoretical studies.